The extent and cost of potentially avoidable admissions in hospital inpatients with palliative care needs: a cross-sectional study. Issue 3 (9th September 2014) - Robinson, Jackie; Boyd, Michal; O'Callaghan, Anne; Laking, George; Frey, Rosemary; Raphael, Deborah; Snow, Barry; Gott, Merryn
Abstract : Objective: More than 90% of people spend time in hospital in the last year of life and, in many developed countries, hospitals are the setting in which most people will die. Previous research indicates that a proportion of these hospital admissions could have been avoided. The objective of this study was to establish the extent and cost of potentially avoidable hospital admissions among patients with palliative care needs. Methods: A prospective survey of hospital inpatients was undertaken to identify patients who met clinical criteria indicating palliative care need. Case notes were reviewed by two expert palliative care clinicians to determine if the hospital admission was potentially avoidable. An analysis of the cost of potentially avoidable admissions compared to all other admissions for those patients identified as being in the last year of life was carried out using the statistical analysis software R V.2.15.1. Logistic regression was performed using the logit (log of OR) link. The binary outcome of the logistic regression model was a potentially avoidable admission. Results: Of the 99 patients who met the criteria for palliative care need, 22 were deemed to have experienced a potentially avoidable admission. Those living in a residential aged care facility were more at risk of experiencing such admissions. The mean total cost of hospital care for those with palliative care needs was lower for those whose admission was deemed potentially avoidable. Conclusions: A significant proportion of patients with palliative care needs experience a potentially avoidable admission. Although these admissions are relatively short compared to those whose admissions are unavoidable, any hospital admission impacts on the experiences of patients and families and may contribute to unnecessary hospital expenditure.